Pharmacogenetics in Psychiatry: An Update on Clinical Usability - van Schaik, Ron H. N.; Müller, Daniel J.; Serretti, Alessandro; Ingelman-Sundberg, Magnus (Frontiers in Pharmacology, 2020)
Using pharmacogenetics in guiding drug therapy experiences a steady increase in uptake, although still leads to discussions as to its clinical use. Psychiatry constitutes a field where pharmacogenomic testing might help in guiding drug therapy. To address current challenges, this minireview provides an update regarding genotyping (SNP analysis/arrays/NGS), structural variant detection (star-alleles/CNVs/hybrid alleles), genotype-to-phenotype translations, cost-effectiveness and actionability of results (FDA/CPIC/PharmGKB) regarding clinical importance of pre-emptive pharmacogenomic testing for prescription of antidepressants and antipsychotics